решите систему уравнений {xy=-12, {(x-2)(y-4)=-8 заранее

решите систему уравнений {xy=-12,
{(x-2)(y-4)=-8 заранее

  • xy=-12

    (x-2)(y-4)=-8

    xy=-12

    xy-4x-2y+8=-8

    y=-12/x

    x(-12/x)-4x-2(-12/x)=-16

    -12-4x+24/x=-16

    (24-4x)/x=-4

    24-4x=-4x

    4x-4x-24=0

    y=-12/-2=6;

    y=-12/3=-4.

    Ответ: (-2;6), (3;-4).

  • раскиваем скобки во втором уравнении(x-2)(y-4)=-8

    ху-4х-2у+8=-8 заменяем xy=-12

    -12- -4х-2у +8=-8 упрощаем

    у=2-2х подставляем в первое уравнение

    х( 2-2х)=-12

    2х-2х^2+12=0 упрощаем

    х^2-х-6=0

    х=3 у=2-6=-4

    х=-2 у=2+4=6